Assessing biomass-fired gas turbine power plants: a techno-economic and environmental perspective - Ihiabe, Daniel (Cranfield University, 2013)
Fossil fuels continue to deplete with use as they are irreplaceable. In addition, the environmental impact with the continuous use of these conventional fuels has generated global concern due to the production of harmful emission gases. An alternative source of energy has become inevitable. Technological advancements in the area of biomass use for both aviation and power generation are at different levels of development. There is however the need for an integrated approach to assess gas turbine engine behaviour in terms of performance, emission and economics when they are running on biofuels. The current research work is concerned with finding alternative fuel resources for use on stationary gas turbine engines for power generation with the necessary identification of suitable biofuels using a multidisciplinary approach. A techno-economic, environmental and risk assessment (TERA) model comprising the performance, emissions, economics and risk modules has been developed. There had been several simulations of two gas turbine engines (GTEs) to ascertain the effects of both ambient and operating conditions and the effect of fuel types on the engines. These simulations were done with the use of an in-house code-the Turbomatch and a code developed for the steam cycle which is employed for the combined cycle simulation. Cont/d.
Keywords: Biomass; Biomass Integrated Gasification combined Cycle; Techno-economic; Risk Analysis; Emissions